Influence of Agricultural Financing Awareness on Financial Problems of Agricultural Entrepreneurs - Newar, Purnima; Anjan Bhuyan (Journal of Extension Education, 2022)
Agribusiness is characterized by uncertain returns and thus it confronts the agricultural entrepreneurs with various situations that impede their capital requirement. This paper attempts to understand the financial problems of agricultural entrepreneurs and to make a relational analysis of their awareness of agricultural financing with their financial problems. The study was conducted in Assam, situated in the northeastern part of India. Multi-stage sampling was used to reach 96 agricultural entrepreneurs. It was found that the inadequate savings and cumbersome process in applying for a loan were the major causes of financial problems of agricultural entrepreneurs and 64% of agricultural entrepreneurs have medium level of awareness on agricultural financing. Analysing the influence of agricultural financing awareness of agricultural entrepreneurs on their financial problems it is concluded that with the increase in the agricultural financing awareness level of agricultural entrepreneurs their financial problems can be reduced to a great extent.